LANDASAN FILOSOFIS PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Khairunnisa Rizka (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2022)
Abstract: The educational process is the path to a better, quality and dignified personal direction. The discussion about character development is a discussion of interesting problems to be studied, especially to make improvements from an early age, starting from elementary school age. We are fully aware that a society of character will be able to become the forerunner of a developed and strong country. Conversely, a country that does not have a good character building will become a country that will experience a decline in various ways. The method in this study uses a narrative-philosophical type qualitative approach. This research uses an interpretive paradigm, namely the collection of data from nature (natural setting) as the main / core data through reading books in the study of the philosophy of character education. The data in this study analyzes and develops the character of learners. what are some of its supporting and inhibiting factors and philosophical views. Methods The foundation of philosophy in character development becomes a direction for the development of character itself in the process of Education. Education is a conscious and planned effort in the process of building a person's character towards a better direction. The philosophical basis of character education is threefold, namely the ontological, epistemological, and axiological basis. There are three kinds of schools in educational philosophy, namely: Progressivism, Essentialism, and Existentialism which greatly influence the character development of children of primary school age today.Keywords: Philosophy; Character development; Character